Gas chromatograph with digital processing of a thermoconductivity detector signal - HADLEY VINCE B; DILBECK RODNEY WAYNE (2014)
A gas chromatograph operable to analyze a sample gas comprising a carrier gas and components. The gas chromatograph includes a bridge circuit with a sample sensor connected therein. A servo amplifier is connected to the bridge circuit and is operable to maintain the sample sensor at a constant temperature. An output of the servo amplifier is digitized and is used to quantify the components in the sample gas.